Penerapan Basel Convention On Plastic Waste Amendments 2019 dalam Upaya Pengurangan Sampah Plastik Impor di Indonesia - Nufus, Aulan; Jayakusuma, Zulfikar; Diana, Ledy (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: The government has uncovered thousands of cases of smuggling of imported waste that violates regulations during the 2019-2022 period, these violations are in the form of waste that cannot be recycled and contains B3, this violates the provisions of the Basel Amendments 2019 based on attachments II, VIII and IX. The environmental damage caused by plastic waste is becoming increasingly serious, because apart from having to overcome existing waste problems, the government also has to face problems related to imported plastic waste. Purposes of the Research: To find out the implementation of the Basel Convention on Plastic Waste Amendments 2019 in efforts to reduce imported plastic waste in Indonesia and to find out the impact of imported plastic waste and the efforts made to reduce imported plastic waste in Indonesia. Methods of the Research: The research method used is a normative research method, namely legal research carried out by examining library materials or secondary data. Results Originality of the Research: The implementation of the Basel Convention on Plastic Waste Amendments 2019 in efforts to reduce imported plastic waste in Indonesia appears to have not been able to be actualized optimally, due to a lack of supervision in its implementation, and there are still gaps that provide opportunities for imported plastic waste to enter Indonesia. The impact of imported waste that continues to enter Indonesia has the potential to damage the environment in Indonesia which will affect the quality of life of future generations. One step is to maximize efforts to sort and process waste, so that in the future we can significantly reduce dependence on imported plastic waste, so that the objectives of the principle of sustainable development can be implemented.